Journal of Pediatric Nursing: Nursing Care of Children and Families Vol.30 Issue 5, September/October 2015 Editor, Cecily Lynn Betz - Redaksi (Elsevier, 2015)
- Transition From Child to Adult Care - 'It's Not a ne-Off Event' : Development of Benchmarks Improve the Experience Susie Aldiss, Judith Ellis, Hilary Cass, Tanya Pettigrew, Laura Rose, and Faith Gibson - Moving in Journey Toward Independence : Adolescents Transitioning to Successful Diabetes Self-Management Elizabeth Babler and Carolyn June Strickland -...